2009
DOI: 10.1002/adsc.200900293
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole Synthesis Using a Titanium‐Catalyzed Multicomponent Coupling Reaction and Synthesis of Withasomnine

Abstract: The titanium-catalyzed 3-component coupling of an alkyne, isonitrile, and amine can be used to generate tautomers of 1,3-diimines. These di-A C H T U N G T R E N N U N G imines produced in situ undergo cyclization with hydrazine and hydrazine derivatives in a one-pot procedure to provide pyrazoles. Seventeen examples of pyrazoles are provided using this one-pot, 4-component procedure from simple starting materials. The regioselectivity of the alkyne addition can be controlled in some cases with catalyst archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 87 publications
1
29
0
4
Order By: Relevance
“…To date, there are many reports available describing the synthesis of pyrazole and pyrazolone derivatives (Batten and Robson, 1998;Liu et al, 2004;Majumder et al, 2009;Uzoukwu et al, 1998;Zhang et al, 2010;Zheng et al, 2009Zheng et al, , 2010. However, there are only few reports on the synthesis of bispyrazole and bispyrazolone derivatives (Deb et al, 2009;Mabkhoot, 2009;Niknam et al, 2010;Tewari et al, 2010;Veettil and Haridas, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…To date, there are many reports available describing the synthesis of pyrazole and pyrazolone derivatives (Batten and Robson, 1998;Liu et al, 2004;Majumder et al, 2009;Uzoukwu et al, 1998;Zhang et al, 2010;Zheng et al, 2009Zheng et al, , 2010. However, there are only few reports on the synthesis of bispyrazole and bispyrazolone derivatives (Deb et al, 2009;Mabkhoot, 2009;Niknam et al, 2010;Tewari et al, 2010;Veettil and Haridas, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…This can be conducted in a one-pot procedure (Scheme 15.114). This strategy was expanded by Odom [350], who showed that Ti-pyrrolyl complexes can also be used in a multicomponent coupling reaction to prepare a variety of pyrazole products. In this case, the coupling of an alkyne, isonitrile, and amine results in the synthesis of the tautomer of 1,3-dimines in situ, which can then undergo cyclization with parent hydrazine and hydrazine derivatives to furnish the targeted pyrazoles in one-pot procedure (Scheme 15.115).…”
Section: N-heterocycle Synthesismentioning
confidence: 99%
“…Not only late transition metals have useful application in total synthesis, but as Odom [350] has shown, Ti-catalyzed multicomponent coupling reactions can also be used to great advantage in the efficient synthesis of the alkaloid withasomnine. In six steps, this pyrazolyl natural product is assembled in 24% overall yield from the commercially available 4-pentyn-1-ol (Scheme 15.124).…”
Section: Total Synthesismentioning
confidence: 99%
“…24) Because of these interesting biological activities, several reports of the synthesis of 1a were disclosed. [27][28][29][30][31][32][33][34][35][36] In the course of our synthetic studies of small natural products and their analogues, [37][38][39][40][41][42] we recently reported the divergent synthesis of withasomnines 1a-c and their analogues via 4-hydroxypyrazole intermediates in a preliminary communication. 43) We herein describe the details of the divergent synthesis of natural 1a-c as well as nine withasomnine analogues 1d-l, which were easily prepared by the Suzuki-Miyaura coupling of key intermediate 16.…”
mentioning
confidence: 99%